Selection of plus tree based on growth performance and fiber morphology characteristics as improved sources for propagation of Eucalyptus camaldulensis - Qader, Nozad Ali; Ab Shukor, Nor Aini; Muhammad Roseley, Adlin Sabrina (Scientific Research Publishing, 2014)
One of the most successful techniques in planting trees is tree improvement in which trees with high qualities are selected for mass plantation. This study seeks to identify good properties of Eucalyptus camaldulensis through selective phases. Sixty Eucalyptus camaldulensis trees (30 ten-year-old and 30 five-year-old) were randomly selected through stratified sampling from two plantation sites in Kurdistan region, North of Iraq. The trees were examined for fiber morphology and quality parameters such as height, number of branches, diameter and straightness. In the first phase of property selection, sixteen trees with high rank in growth properties and fiber morphology were selected. In the final phase of selection, the selected trees were re-examined according to the number of properties and fiber morphology features and seven trees with the highest number of good parameters were chosen. The 7 selected trees had higher qualities in growth characteristics and fiber morphology compared with the other trees in the sample. This article reports on a selection method for E. camaldulensis trees through tree improvement techniques. The results of the study indicates that high genotype qualities were identified among both 5- and 10-year-old E. camaldulensis trees as the final selection consisted of three 5-year-old trees and four 10-year-old trees.